Non-meningeal tumours of the cavernous sinus: A surgical analysis - (:unkn) unknown (ELSEVIER SCI LTD, 2006)
The popularisation of cavernous sinus approaches and subsequent experience has shaped our treatment paradigms for cavernous sinus meningiomas. However, pathologies in this region are diverse and each one requires individual consideration. The purpose of this study was first to analyse, define and summarise the individual characteristics of different non-meningeal tumours of the cavernous sinus and, secondly, to stress that their surgery can be accomplished with acceptable morbidity and rewarding results when those characteristics are considered. A retrospective analysis of 42 cases of benign non-meningeal tumours of the cavernous sinus operated on at Marmara University between April 1992 and April 2003 is presented. The patients were 15 males and 27 females aged 24-72 years. The study cohort consisted of 13 pituitary adenomas, 11 trigeminal schwannomas, seven chordomas, three chondro sarcomas, two juvenile angiofibromas, two epidermoid tumours, one plasmacytoma, one cavernous haemangioma and one internal carotid plexus schwannoma. The 42 patients underwent 46 operations aimed at radical surgical excision. Total resection was achieved in 50% and subtotal resection in 50% of cases. The majority of incompletely resected tumours were pituitary adenomas and chordomas, and 95% required further treatment. Twenty-nine percent of patients developed complications, namely cerebrospinal fluid fistula, haematoma, hydrocephalus, diabetes insipidus, cerebral infarction and cranial nerve palsies. Recurrence was seen in 7.1% of patients. At final follow up at an average of 48.2 months after surgery, the mean Karnofsky performance scale had risen from 83.4 to 87.4. Non-meningeal tumours of the cavernous sinus can be surgically resected with acceptable morbidity and mortality. In selected tumours the results are better than those for cavernous sinus meningiomas. The best surgical results are achieved with interdural tumours of the lateral sinus wall and the worst surgical results are seen in invasive tumours such as chordomas and pituitary adenomas. Individual tumour characteristics are presented in the text. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: cavernous sinus; pituitary adenoma; trigeminal schwannoma; chordoma; skull base surgery; JUVENILE NASOPHARYNGEAL ANGIOFIBROMA; LATERAL SELLAR COMPARTMENT; INTERNAL CAROTID-ARTERY; SKULL-BASE CHORDOMAS; TRIGEMINAL SCHWANNOMAS; EXTRADURAL APPROACH; STEREOTACTIC RADIOSURGERY; PITUITARY-ADENOMAS; GASSERIAN GANGLION; EPIDURAL APPROACH